Symptom experiences of older adults during treatment for metastatic prostate cancer: A qualitative investigation. Issue 1 (January 2023) - Parthipan, Milothy; Feng, Gregory; Toledano, Nelly; Donison, Valentina; Breunis, Henriette; Sudharshan, Abirami; Emmenegger, Urban; Finelli, Antonio; Warde, Padraig; Soto-Perez-de-Celis, Enrique; Krzyzanowska, Monika; Matthew, Andrew; et al.
Abstract: Introduction: Exploring symptom experiences of older men during metastatic prostate cancer treatment can help clinicians identify unmet supportive care needs that, if addressed, could improve toxicity management and enhance patient wellbeing. Previous qualitative studies of older adults with advanced prostate cancer have focused on the psychological experience rather than the overall symptom experience. Therefore, the objective of this study was to understand the lived experience of symptoms and supportive care needs in older men undergoing treatment for metastatic prostate cancer. Materials and Methods: Semi-structured interviews were conducted with older adults (aged 65+) who completed their first cycle of chemotherapy, androgen-axis targeted therapies, or radium-223 for metastatic castrate-resistant and sensitive prostate cancer at the Princess Margaret Cancer Centre, Toronto, Canada. Six coders worked in pairs to review interview transcripts and conduct a thematic analysis. A consensus was reached through team discussions. Topics of interest included symptom experiences, the impact of symptoms on daily life, symptom management strategies, and suggestions for external support. Results: Thirty-six interviews were conducted with older adults (mean age: 76 years, 92% with metastatic castrate-resistant prostate cancer) who started chemotherapy ( n  = 11), androgen-axis targeted therapies ( n  = 19), or radium-223 ( n  = 6). The most common treatment-specific symptoms included: fatigue, pain, sleep disturbances, mood disturbances, and gastrointestinal symptoms. Four themes on the impact of symptoms on daily life emerged: resting more than usual, changes in mobility, changes in maintaining activities of daily living, and not feeling up to most things. It is important to note that participants who underwent chemotherapy have previously completed other lines of treatment and had more advanced disease, possibly contributing to higher prevalence of symptoms and greater impact on daily life. Four themes on symptom management strategies emerged: positive support systems, seeking help, interventions by healthcare providers, and self-management strategies. Suggestions for external support included building social support networks, improving health literacy, improving continuity of care, receiving support from healthcare providers, engaging in health-seeking behaviours, and addressing unmet supportive care needs. Discussion: Exploring symptom experiences of older men with metastatic prostate cancer provides valuable insights for developing supportive care programs and improving patient care.